Qualitative research on critical issues in Halal logistics / Mohamed Syazwan Ab Talib, Lim Rubin and Vincent Khor Zhengyi - Ab Talib, Mohamed Syazwan; Rubin, Lim; Zhengyi, Vincent Khor (Universiti Teknologi Mara Selangor, 2013)
Halal is not only restricted to Muslims and is more than a religious matter. Halal is in the realm of business and trade, and is becoming a global symbol for quality assurance and lifestyle choice. Although Halal is booming and on an upward trend, there are very limited studies published on Halal logistics and academic research in this area is highly needed. This study is exploratory in nature and data are collected through series of focus groups interviews. Besides that, this study applies purposive sampling and judgement sampling as information are conveniently available from specific target groups. Results obtained from this study uncover the various issues faced by Halal logistics service providers and are categorized into five categories namely general Halal issues (BARRIER 1), integration issues among logistics service providers (BARRIER 2), integration issues between Halal authorities and logistics service providers (BARRIER 3), financial issues and perception of implementing Halal logistics (BARRIER 4) and issues pertaining to government’s support and promotion (BARRIER 5). The researcher managed to underline the research limitation such as the lack of empirical evidence, lack respondents from non-logistics companies and the study only focuses on Halal logistics thus ignoring other Halal businesses such as Halal pharmaceutical and Halal tourism. Plus, the issues uncovered open more doors for potential future research on barriers and critical success factors in adopting Halal into logistics management.